Fluorescence Microscopy Visualization of Contacts Between Objects1. Issue 12 (28th January 2015) - Suhina, Tomislav; Weber, Bart; Carpentier, Chantal E.; Lorincz, Kinga; Schall, Peter; Bonn, Daniel; Brouwer, Albert M.
Abstract The area of contact between two objects was detected by using the strong enhancement of the fluorescence of rigidochromic probe molecules attached to one of the surfaces. Confinement of the molecules suppresses nonradiative decay and turns on the fluorescence. The approach is demonstrated by imaging of the contact area of a plastic sphere in contact with a flat glass surface. Our results agree excellently with the prediction of Hertz's classical theory based on elastic deformation.